Human capital: valuation and management - Chernov Vladimir (E3S Web of Conferences, 2023)
The article considers approaches to the assessment of human capital taking into account the concept of value-oriented corporate management, which has become the methodological basis of the study. The tools of synthetic and analytical accounting in accordance with RAS and the tax legislation of the Russian Federation were used to disclose the content and comprehension of the studied financial notions. The methods of relative values of economic analysis, quantitative methods of evaluation, cost-based (property), revenue and market (comparative) approaches are used in relation to determining the value of human capital. A more specific definition of the human capital utilization coefficient and quantitative estimates of individual human capital, goodwill of human capital are proposed. A universal methodology has been developed for assessing human capital in proportion to the business qualities and labor contribution of employees to the capitalization of the enterprise and the increase in its value. The proposed methodology integrates revenue, cost-based (property) and market approaches. The quantitative relationship between the goodwill of individual human capital and the goodwill of the entire enterprise is revealed. For practitioners in the field of business valuation, researchers in the development of value-oriented corporate management, teachers and students of economics in the study of financial methods of corporate valuation.